Review of Thematic Bureaucratic Reform Policy Changes in Efforts to Accelerate Local Development in Indonesia - Khairul Muluk, M.R.; Radyan Danar, Oscar; Amiruddin, Akhmad (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Bureaucratic reform has become the Indonesian government's strategic agenda to create better, more adaptive and responsive governance. In the context of bureaucratic modernization, the Weberian bureaucratic model which emphasizes hierarchy, professionalism and standard rules is seen as less effective in dealing with global dynamics and local complexity. Therefore, thematic bureaucratic reforms have emerged that focus on improving the quality of public services, infrastructure development, and accelerating community welfare. This research examines the impact of implementing thematic bureaucratic reform on accelerating development at the local level, especially in three main aspects: public services, infrastructure development, and improving the quality of life of the community. It is hoped that thematic bureaucratic reform can build a bureaucracy that is responsive, fast and adaptive, in accordance with the directions of the President of Indonesia. Although the concept of thematic bureaucratic reform is promising, its implementation still faces challenges at the regional level. Many local governments view these reforms as an additional burden, with little understanding of their implementation. Therefore, further efforts are needed in the form of outreach, assistance and technical training for local governments, so that the Thematic RB can be implemented more effectively and sustainably.